Slovenian test case Vrbanski Plato aquifer in the EU HORIZON 2020 FREEWAT project - Kopa?, Irena; Vremec, Matevž (Acque Sotterranee - Italian Journal of Groundwater, 2017)
The Slovenian case study in the EU HORIZON 2020 FREEWAT project was Vrbanski Plato aquifer. Slovenia is divided into two river basin districts: the Danube and the North Adriatic. The Vrbanski Plato aquifer, which he presents both natural and artificial bank filtration from the river Drava, is a part of the Danube river basin district and is the most important water source for 14 municipalities in the northeastern part of Slovenia. We investigated the groundwatersurface water interaction between river Drava and the porous aquifer in the geological old riverbed and possible reduction of city impact. This site is the oldest managed artificial groundwater recharge with riverbank filtration and has more than thirty years of successful operation. It is something special, very abundant in a small space, independent of drought and climate changes, but vulnerable due to the impact of the city. Under the city there is watershed dividing, which is shifting with different water management condition and we would like to have the least possible impact of the city. For optimal water management we decided to use FREEWAT plug-in within QGIS platform. With new developed FREEWAT plug-in in project FREEWAT, we made steady-state and transient groundwater model for presenting this shift of the watershed dividing under the city and optimal water management for this area. The model was designed in a way that it identifies and describes all major aspects of the physical hydrogeological system and water management. During the running of a project, there was an accident with heating oil spillage in city area, right on the watershed dividing. So we oriented with the transient groundwater model as well on heating oil spillage and pumping with additional wells at the place of the accident to present successful rehabilitation and the importance of the managed groundwater recharge. Our experience with FREEWAT platform during the Vrbanski Plato aquifer case study was very positive. The connection data of the GIS tool, open license and the database monitoring and model approaches functioned as the right tool for a professional approach and communicating with stakeholders. With groundwater models in FREEWAT platform, we defined optimal condition, with as less as possible the impact of groundwater below the city, for pumping water on the Vrbanski Plato, managed by Water Supply Maribor company and needed optimal level in river Drava managed by Drava Power Plants Company. Quantities of pumping for water supply and level of Drava River are the dominant components of water management in this area. Due to the time and financial constraints, we took into account the period from July 2014 to June 2017.